A Clinical Extensively-Drug Resistant (XDR) Escherichia coli and Role of Its β-Lactamase Genes - Wang, Mingyu; Wang, Wenjia; Niu, Yu; Liu, Ting; Li, Ling; Zhang, Mengge; Li, Ziyun; Su, Wenya; Liu, Fangyue; Zhang, Xuhua; Xu, Hai (Frontiers in Microbiology, 2020)
An extensively-drug resistant (XDR) Escherichia coli W60 was isolated from the urine sample of a patient. The genetic basis for its XDR phenotype was investigated, particularly the basis for its resistance toward β-lactam/BLI (β-Lactamase Inhibitor) combinations. Following determination of the XDR phenotype, third generation genomic sequencing was performed to identify genetic structures in E. coli W60. Further cloning analysis was performed to identify determinants of β-lactam/BLI combination resistance. It was found that E. coli W60 is resistant to nearly all of the tested antibiotics including all commonly used β-lactam/BLI combinations. Analysis of the genomic structures in E. coli W60 showed two novel transferable plasmids are responsible for the resistance phenotypes. Further genetic analysis showed blaNDM–5 leads to high resistance to β-lactam/BLI combinations, which was enhanced by co-expressing bleMBL. pECW602 harbors a truncated blaTEM that is not functional due to the loss of the N-terminal signal peptide coding region. Research performed in this work leads to several significant conclusions: the XDR phenotype of E. coli W60 can be attributed to the presence of transferable multidrug resistance plasmids; NDM-5 confers high resistance to β-lactam/BLI combinations; co-expression of bleMBL enhances resistance caused by NDM-5; the signal peptides of TEM type β-lactamases are essential for their secretion and function. Findings of this work show the danger of transferable multidrug resistance plasmids and metallo-β-lactamases, both of which should be given more attention in the analysis and treatment of multidrug resistant pathogens.